A new species of Culex (Melanoconion) from Southern Brazil (Diptera: Culicidae) Nova espécie de Culex (Melanoconion) da região meridional do Brasil (Diptera: Culicidae) - Oswaldo Paulo Forattini; Maria Anice Mureb Sallum (Universidade de São Paulo, 1985)
A new species from Southern Brazil, named Culex (Melanoconion) ribeirensis is described. The description includes adults, pupal and larval stages, illustrating the morphological aspects and a picture of a breeding place. Some data about known distribution and bionomics are presented. Descreve-se nova espécie, denominada Culex (Melanoconion) ribeirensis, da região meridional do Brasil, incluindo localidades dos Estados de São Paulo e do Rio de Janeiro. A descrição inclui as formas adultas, pupal e larval, e é acompanhada de ilustrações representativas desses estádios, além do aspecto de um criadouro natural. Apresentam-se também alguns dados sobre a distribuição geográfica, até agora conhecida, e do comportamento dessa espécie.